Integrasi Akhlaq Islami dalam Sistem Hukum Nasional untuk Meningkatkan Moralitas Publik - hady, diens (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2025)
The integration of Islamic morals (akhlaq Islami) into the national legal system aims to enhance public morality through the enforcement of Islamic moral and ethical values. Akhlaq Islami, which includes principles of honesty, justice, and social responsibility, is considered crucial for application in various aspects of societal life, including the legal system. The implementation of akhlaq Islami in law can strengthen the moral foundation of society, increase legal awareness, and reduce crime rates. This integration also promotes the creation of a more harmonious and just social environment. This research is a qualitative study with a descriptive-analytical approach. The qualitative approach is used because this study focuses on an in-depth exploration of concepts, perceptions, and experiences related to the integration of akhlaq Islami in the national legal system. The research findings indicate that Indonesian society generally supports the integration of Islamic values into the legal system, as they believe that the principles of akhlaq Islami can improve individual morality and legal justice. Although there are concerns about inconsistency and discrimination, public support remains important. Legal education that integrates Islamic values can shape more ethical students, although its implementation is still limited. The main challenges are differences in interpretation, resistance from secular groups, and lack of political support, which require dialogue and cooperation. The role of religious scholars (ulama) and religious institutions is crucial in shaping legal policies that align with Islamic values.